Pengaruh Debt To Equity Ratio, Total Assets Turnover, Dan Volume Penjualan Terhadap Profitabilitas Pada Perusahaan Property Dan Real Estate Yang Terdaftar Dalam Bursa Efek Indonesia - Desy Anwar Desy (Fakultas Ekonomi Prodi Akuntansi, 2020)
The main objective of this study is to examine the effect of debt to equity ratio, total asset turnover, and sales volume on profitability in property and real estate companies listed on the Indonesia Stock Exchange in 2013-2017. debt to equity ratio is the ratio chosen from the solvency ratio that can reflect a company's ability to meet all its financial obligations both long-term and short-term. Asset turnover is the ratio chosen from the activity ratio aimed at measuring the level of effectiveness of the company in using operating assets. Sales volume is based on the total sales the company gets. Profitability aims to measure how much the company's ability to generate profits. The population of property and real estate companies consists of 48 companies and the number of research samples consists of 27 property and real companies in 2013-2017 determined through the purposive sampling method using certain criteria. The method used in this research is quantitative, the type of research used is descriptive, the nature of this study is causal and the type of data is secondary obtained through the Indonesian stock exchange. This research was conducted with multiple regression analysis and classical assumption test. The classic assumption test consists of a normality test, a multicollinearity test, an autocorrelation test and a heteroscedasticity test. The results of this study indicate that the debt to equity ratio has a negative and significant effect on profitability, total assets turnover has a positive and significant effect on profitability and sales volume has a positive and not significant effect on profitability. debt to equity ratio, total asset turnover and sales volume simultaneously influence the profitability of porperty and real estate companies listed on the Indonesia Stock Exchange for the period 2013 - 2017.